Surface-strip coal mine rehabilitation risk assessment : the development of an integrated rehabilitation risk assessment model for use in South Africa and Australia - Truter, Wayne Frederick (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2020.